Simulation of patient flow and optimization of bed allocation for a Singapore public hospital - Wang, Zhuojun (Nanyang Technological University, 2020)
To help hospital managers better understand bed demand in Department of Surgery(DOS) and make bed management decisions, a Discrete Event Simulation(DES) model to simulate patient flow through wards in DOS is constructed based on a careful study of historical data on patient arrival pattern, patient length of stay and patient distribution among wards. The model is evaluated to be able to perform relatively well through comparison of simulated data with actual data. A greedy bed allocation algorithm is adopted to allocate beds among wards as well and an optimal bed allocation which can achieve maximum bed utilization rate is obtained.